Importance of the Community Partner Role at NOSC 2012 - Felecia Jones (The University of Alabama, 2022)
NOSC 2012 had many firsts, including the largest conference in the organization's 13-year history and the highest number of community partner participants. But the real breakthrough was the emerging understanding and respect scholars and community partners developed for each other, which came home in a variety of ways, from the number of community partners attending to the "ah ha" moment when one delegate first understood how essential community partners are to all aspects of engaged scholarship.